1997
DOI: 10.1086/523996
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Retinoblastoma in a Male Patient with an X;13 Translocation: Evidence for Silencing of the RB1 Gene by the Spreading of X Inactivation

Abstract: HH, et al. (1995)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 11 publications
(20 reference statements)
1
8
0
Order By: Relevance
“…In all cases where blood was screened with a negative result, we have checked for promoter methylation. Again, none was found in this cohort although we have subsequently seen promoter methylation in one patient carrying an X;13 translocation (unpublished data) as previously reported by Jones et al 39. Of the 27 tumours found to be methylated, 13 had LOH (48%) while 14 (52%) did not.…”
Section: Discussionsupporting
confidence: 84%
“…In all cases where blood was screened with a negative result, we have checked for promoter methylation. Again, none was found in this cohort although we have subsequently seen promoter methylation in one patient carrying an X;13 translocation (unpublished data) as previously reported by Jones et al 39. Of the 27 tumours found to be methylated, 13 had LOH (48%) while 14 (52%) did not.…”
Section: Discussionsupporting
confidence: 84%
“…In cases of X;autosome translocation the X inactivation signal may spread variably into an attached autosomal segment, with the translocated portion of autosome adopting features of the adjacent inactivated X chromatin (Jones et al 1997;Keitges and Palmer 1986). Many studies have shown that such translocated autosomal material can become delayed in its replication timing, and this feature is commonly used as a marker to define the extent of spread of X inactivation in such cases.…”
Section: Introductionmentioning
confidence: 99%
“…In RB tissues, methylation of a CpG island (CpG106) encompassing the promoter region of RB1 is a quite frequent mechanism inactivating one copy of the gene (13%) but the same event in patients’ nontumor cells has been rarely described (Greger et al., ). In 1997, a first report provided evidence that RB can develop in the context of a X;13 translocation spreading X inactivation to chromosome 13 and producing functional monosomy for genes on proximal 13q including RB1 (Jones et al., ). A more recent study reported a possible constitutional methylation of the RB1 promoter as cause of hereditary RB; however such results have been questioned by Sloane and colleagues, in a subsequent letter on the same journal, given the lack of all the criteria necessary to demonstrate the presence of an epimutation (Quinonez‐Silva et al., ; Sloane, Ward, & Hesson, ).…”
mentioning
confidence: 99%